THE DYNAMICS OF INCOME INEQUALITY IN THE SOLO RAYA REGION, 2008-2020 - Nanda Adhi Purusa; Miftachul Mujib; Joni Prayogi; Fahrein All Sandra (Pusat Riset dan Inovasi Nasional, 2021)
This study examines the effect of growth of the manufacturing sector, the human development index, and inflation on income inequality in the Solo Raya Region in 2008-2020. This study used panel data analysis with six districts and one city member of the Solo Raya Region. The data analysis stage was a selection test of the estimation technique and the classical assumption test to produce the best panel data regression model with the SUR cross-section weight. The regression estimation shows that the growth of the manufacturing sector and inflation positively and significantly affect income inequality. The human development index shows a negative and significant impact on income inequality. This analysis indicates that the economic development process in the Solo Raya region is in line with the development stages based on Rostow's view. The positive relationship between growth in the manufacturing sector and income inequality shows similarities to Kuznets's hypothesis that income inequality will increase in the initial phase of economic growth.